Transcriptomic analysis reveals the immune response of human microglia to a soy protein and collagen hybrid bioscaffold. Issue 2 (February 2023) - Yao, Li; Blasi, Jacques; Shippy, Teresa; Brice, Ryan
Abstract: Inflammatory reactions resulting from spinal cord injury cause significant secondary damage. Microglial cells activate CD4 + T cells via major histocompatibility complex class II (MHCII) molecules. The activated T cells lead to neural tissue damage and demyelination at early stages of spinal cord injury. Control of the inflammatory response may attenuate the injury process. In this study, we compared gene expression in human microglia grown on soy protein-collagen hybrid scaffolds versus collagen scaffolds. Differentially expressed genes (DEGs) were subjected to gene ontology (GO) and pathway enrichment assays. Among down-regulated genes, the "antigen processing and presentation" pathway shows enrichment, primarily due to the down-regulation of MHCII molecules. The DEGs in this pathway show enrichment of binding sites for several transcription factors, with CIITA and IRF8 being the top candidates. The down-regulation of MHCII along with the significant enrichment of the GO term "focal adhesion" among the up-regulated genes helps explain the higher motility of microglial cells on the hybrid scaffold compared with that on the collagen scaffold. Up-regulated genes associated with "focal adhesion" include DNM2, AHNAK, and HYOU1, which have been previously implicated in increased cell motility. Overall, our study indicates that the use of hybrid scaffolds containing soy protein and collagen may modulate the immune response of wounded neural tissue.